Before the First Draft: A Mixed-Methods Needs Analysis of EFL Student Interest in A Positive Psychology-Based Professional Writing Course - Nur, Sahril; Nurfadhilah, Auliyanti Sahril; Sakkir, Geminastiti (Pascasarjana Universitas Negeri Makassar, 2025)
This mixed-methods study analyzes the need for a professional writing course for L2 students based on Positive Psychology (PP). It surveyed 70 third-semester EFL students at Universitas Negeri Makassar, categorized by academic achievement, on their interest in a PP-based curriculum focusing on Meaning, Accomplishment, Relationships, and Engagement. While all students showed high interest in the course's career relevance, significant differences emerged in their reception of PP pedagogy. Low-achieving students were most interested in strengths-based, confidence-building aspects, often due to past negative feedback experiences. High-achieving students were more motivated by authentic, real-world challenges. The findings reveal that even innovative pedagogies are not one-size-fits-all, highlighting the necessity of a pre-curricular diagnostic approach to meet the diverse cognitive and affective needs of students.